THE CONCEPT OF LOVE: A COMPARATIVE STUDY OF MAULANA RUMI AND SHAH ABDUL LATIF BHITTAI - Ali Lashari, Mubarak; Awan, Muhammad Safeer (European Scientific Journal, ESJ, 2014)
In this comparative study, it is tried to explore some parallels of the concept of love between two great mystic poets, i.e. Maulana Rumi and Shah Abdul Latif Bhittai. Instead of several differences in their perspectives like, homeland, language and bringing up in different social environment and backgrounds, there is clear manifestation of the similarities in their philosophies. Through this research it can be seen that Shah Abdul Latif Bhittai seems as a spiritual disciple of Maulana Rumai; consequently this vision has been the main focus of investigation.